Hepatitis E virus infection in Hong Kong blood donors. Issue 1 (10th November 2019) - Tsoi, Wai‐Chiu; Zhu, Xiaomei; To, Amanda Pui‐Chi; Holmberg, Jerry
Abstract : Background and Objectives: In Hong Kong, the dominant circulating hepatitis E virus (HEV) genotype is type 4, which can cause more severe clinical consequences than type 3. The aim of this study was to determine the HEV prevalence in Hong Kong blood donors. Materials and Methods: Unlinked donation samples ( n = 10 000) collected in March to May 2015 were tested for HEV RNA using the Procleix HEV assay in an individual donation format (IDT). A subset of 2000 samples were tested for IgG and IgM anti‐HEV using the Wantai enzyme‐linked immunosorbent assay (ELISA). Nucleic acid testing (NAT) initial reactive results were retested once, and repeatedly reactive donations were subjected to alternative molecular procedures as confirmation tests. Results: One in 5000 Hong Kong blood donors was positive for HEV RNA (0·02%). The two RNA positive samples were also IgG and IgM anti‐HEV positive. One of the two RNA positive donors could be sequenced revealing genotype type 4. Anti‐HEV seroprevalence was estimated as 15·5% among all donors. IgG anti‐HEV positive rate for age group 16–20 was 3·1%, and it increased with age to 43·1% for age group 51–60. Sero‐positivity was higher in males (male donors 18·1% vs. female donors 13·2%), but it was mostly due to the difference in a specific age group (41–50). Conclusion: Hepatitis E virus RNA positive rate of 0·02% was within the reported range of HEV RNA frequency in developed countries. One donor was confirmed to be genotype 4, which is the dominant genotype in circulation in Hong Kong.